Kajian Pustaka Potensi Sargassum Sp. Sebagai Nutrasetikal - Reyhan Aryatikta; Sri Winarni; Susatyo Nugroho Widyo Pramono (LPPM Universitas Terbuka, 2022)
Sargassum sp. is a type of seaweed commonly found in Indonesia. Chemical analysis and experimental studies have demonstrated the potential of Sargassum sp. as a nutraceutical, with findings of bioactive compounds with health effects and benefits. This review aims to compile literature about Sargassum sp. to investigate its chemical and bioactive composition, and its effects on health. Based on the current literature results, Sargassum sp. is a source of various bioactive compounds such as fucoidan, laminarin, alginate, fucosterol, phlorotannin, Sargachromenol and fucoxanthin. These compounds has various roles including as antioxidant, antiinflammatory, antidiabetic, antiobesity, antimicrobial, immunomodulator, cytoprotective, gastroprotective, and neuroprotective agent. For that reason, Sargassum sp. has potential for further developments as a nutraceutical.